2010
DOI: 10.3928/01477447-20100722-45
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Metal Reactivity: Houston, We Have a Problem!

Abstract: In this single-surgeon series, both resurfaced hips in 1 woman and a total hip arthroplasty in another were revised for symptomatic pseudotumor (3 of 588 hips; 0.51% overall incidence; 2.2% in women). All 3 hips had 50-mm acetabular components. There was no difference in mean lateral opening angle (mean 38.7° vs 42.8° for the others) but these 3 hips all had increased acetabular anteversion (mean 27.1° vs 16.4° for the others; P<.05). Increased combined anteversion is a mechanical common denominator in pseudot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In terms of metal sensitivity or adverse metal reactions as the primary diagnosis for failure, 4 of 5 patients in the current study who exhibited an adverse metal reaction were women, coinciding with observations in other studies. [11][12][13][14][15] This occurred in 6.5% of the current patient patients who underwent revision. Furthermore, localized soft tissue changes, whether in the setting of metal sensitivity alone or in concert with other failure reasons, were seen in 13% of patients, the majority of whom were women (7/10).…”
Section: Discussionmentioning
confidence: 91%
“…In terms of metal sensitivity or adverse metal reactions as the primary diagnosis for failure, 4 of 5 patients in the current study who exhibited an adverse metal reaction were women, coinciding with observations in other studies. [11][12][13][14][15] This occurred in 6.5% of the current patient patients who underwent revision. Furthermore, localized soft tissue changes, whether in the setting of metal sensitivity alone or in concert with other failure reasons, were seen in 13% of patients, the majority of whom were women (7/10).…”
Section: Discussionmentioning
confidence: 91%
“…Highly crosslinked PE appears to be a good alternative to hard-on-hard bearings, considering that metal-on-metal articulations may cause excessive wear and pseudotumors, and that ALVAL ( Carothers et al 2010 , Schmalzried and Tiberi 2010 ) and ceramic-on-ceramic articulations have been plagued by squeaking ( Sexton et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mokka et al [11] showed a higher rate of ARMD in bigger diameter heads. Various authors [12–14] have suggested a higher rate of ARMD in incorrect acetabular cup placement, in anteversion, or related to greater inclination in the acetabular lateral opening angle. These studies highlight that increased friction in head-cup contact increases the risk of metallosis.…”
Section: Discussionmentioning
confidence: 99%